Modeling and control theory applied to the wine fermentation process - Santana Rosas, Carlos Alberto (2018)
The thesis has two purposes: The first one is to build a mathematical model that better approximates (with respect to the mathematical model in [2]) to the behaviour of the wine fermentation process with the addition of certain amount of nitrogen at some instant of time, based in [2]. This mathematical model is described by mean ordinary differential equations including some parameters which will be identified solving some optimization problems. The second purpose of the thesis is to study the improved model but introducing some control variables in order to stabilize in an appropriated sense the corresponding dynamical system of the new model. This is a kind of MIMO nonlinear system control problems and will be solved using the tools in [6].